The effect of Tofu Wastewater on Cabbage Growth and Preference of Plutella xylostella - Siska Rasiska; Nasya Nabila; Danar Dono; Toto Sunarto; Ceppy Nasahi (CROPSAVER, 2022)
Tofu wastewater containing a high proportion of organic compound may cause various adverse impacts, such as water pollution which bad smell and degrading the aesthetics of the environment.  The efforts uses of tofu wastewater is a organic liquid fertilizer. The aims of this study was to determine the effect of tofu wastewater on cabbage growth and preference of Plutella xylostella. The experiment was carried out from April to June 2018, at Ciparanje Experimental Field, Faculty of Agriculture, Universitas Padjadjaran. Randomized block design was used with nine treatment concentration of tofu wastewater consist of control 0%, 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, 87.5%, 100%, and three replication. The result showed that tofu wastewater by 100% could increase the growth of cabbage. The highest female P. xylostella preference.